PERAN AUDITOR INTERNAL DAN PENGENDALIAN INTERN DALAM PELAKSANAAN TATA KELOLA PEMERINTAHAN YANG BAIK - Astuty, Widia (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
This study aimed at obtain the interpretation of: ( 1) TTte effect o I 1e ro e of I 1e nterna au itor on the good governance implementatg; (2) Effect of internal control on the good governance implementation; and (3) Effect of the role of inlernal auditors and internal control simultaneously 011 the good governance implemenlation. ? , This research method using descriptive and verificative types. T e unit of analysis in this study are all the Provincfl!t Office of North Sumatra. Descriptive analyzes were performed lo obtain a picture of the role of internal auditors and internal control and the implemenlation of good governance. While verificalive analyzes Lo examine the effect of the role of internal auditors and intern.antral partially and simullaneously on the good governance implementation with Path analysis.The results showed Lhat: ( 1) There is the influence of Lhe role of Lhe infernal auditor on the good governance implementation; (2) There is an effect of the i1'Jil'1al controlonthegoodgovernanceimplemenlalion ; and (3) There is Lhe influence of1he role of internal auditors and internal control simultaneously on the good governance implementation.